1994
DOI: 10.1017/s0890037x00028542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicosulfuron Rate, Adjuvant, and Weed Size on Annual Weed Control in Corn (Zea mays)

Abstract: Field experiments were conducted in 1988 and 1989 to (i) evaluate annual weed control with nicosulfuron applied at rates of 17 to 70 g ai/ha with several additives and (ii) evaluate annual weed control with nicosulfuron applied at rates of 17 to 105 g/ha at three corn growth stages. In 1988, in the adjuvant study, giant foxtail control increased linearly with no additive or with urea ammonium nitrate as the rate of nicosulfuron increased. Petroleum oil concentrate, nonionic surfactant, and a combination of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
3
20
0
3
Order By: Relevance
“…However, studies have found that in notillage systems, some invasive species, such as Spermacoce latifolia, Synedrellopsis grisebachii, Commelina benghalensis, and Tridax procumbens, have been selected because of successive glyphosate applications in Cerrado agricultural areas (Procópio, Menezes, Betta, & Betta, 2007). Other weed species were also reported as tolerant to this herbicide: Ambrosia artemisiifolia (Kapusta, et al, 1994), Sesbastiania exaltata, Ipomoea spp. (Jordan & Christoffoleti 1997;Lich, Renner, & Penner, 1997), and Apocynum cannabinum, Asclepsias syriaca (Wyrill & Burnside, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found that in notillage systems, some invasive species, such as Spermacoce latifolia, Synedrellopsis grisebachii, Commelina benghalensis, and Tridax procumbens, have been selected because of successive glyphosate applications in Cerrado agricultural areas (Procópio, Menezes, Betta, & Betta, 2007). Other weed species were also reported as tolerant to this herbicide: Ambrosia artemisiifolia (Kapusta, et al, 1994), Sesbastiania exaltata, Ipomoea spp. (Jordan & Christoffoleti 1997;Lich, Renner, & Penner, 1997), and Apocynum cannabinum, Asclepsias syriaca (Wyrill & Burnside, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Essa redução é ocasionada principalmente pela competição int erespecífica por água, luz e nutrientes (Swanton & Weise, 1991;Kapusta et al, 1994) e, também, pela competição por dióxido de carbono, espaço físico e temperatura (Anderson, 1977).…”
Section: Introductionunclassified
“…Apenas a mistura dos herbicidas atrazine, metolachor e nicosulfuron apresentou níveis inferiores de controle. A limitação do controle de plantas daninhas pela aplicação de herbicidas em pós-emergên-cia pode estar relacionada à necessidade de adjuvantes (Kapusta et al, 1994), à inadequação das doses e às condições ambientais no momento da aplicação. Na avaliação de pré-colheita, os herbicidas aplicados no início do desenvolvimento da cultura apresentaram controle inferior de BRAPL em relação aos demais tratamentos (Tabela 1).…”
Section: Resultsunclassified
“…Os herbicidas utilizados possuem eficiência variável, principalmente em função das condições do ambiente, da época de aplicação e da espécie da planta daninha (Merotto Jr. et al, 1997). Os herbicidas aplicados em pré-emergência podem ter eficiência comprometida, em razão da baixa umidade do solo (Kapusta et al, 1994) e também das variações de textura, das características químicas e dos níveis de cobertura do solo com resíduos vegetais. A eficiência dos herbicidas aplicados em pós-emergência está condicionada, principalmente, às condições climáticas no momento da aplicação e ao estádio de desenvolvimento das plantas daninhas.…”
Section: Introductionunclassified